Організація навчально-виховної роботи у земських школах Харківської губернії (друга половина ХІХ – початок ХХ століття) - Жуков, С. М. (НТУ "ХПІ", 2015)
Розглядається навчальний процес та виховна робота у земських початкових народних училищах на Харківщині у 1865-1917 рр. Проаналізовано зміст навчальних програм, форми навчальної роботи, охарактеризовано систему проведення випускних іспитів. Визначено внесок Міністерства освіти, Харківської дирекції народних училищ та місцевого самоврядування у формування змісту та організацію освітнього процесу. Розглянуто зміст, завдання та основні форми виховної роботи.

The article is a complex research of the organization of educational work in primary peasant schools of the Kharkiv province in 1865-1917. The content, tasks, forms of educational work in primary schools of the Kharkiv province have been characterized. The evolution of the final exams system in zemstvo schools has been described. The part of the Ministry of education, local department of education, local self-government and pedagogical society in the formation and development of educational work has been analyzed. It was found that in educational work in peasant schools different forms of participation in social and ecclesial life have been used. Educational work in rural schools was based on the principles of development of students' traits of Christian piety, humanistic values and instilling patriotic feelings. To achieve this, used various forms of work related to participation in church schools and public life.
The Organization of Educational Work in Zemstvo Schools of the Kharkiv Province at the second half of the 19th – at the beginning of the 20th centuries
Keywords: Харківська губернія; Харків історія; народна школа; діяльність педагогічна; народна освіта; початкова освіта; виховна робота; земство; zemstvo; peasant school; primary education; educational work; final exam